An Outline of the Europe – South Africa Relations During and Post the Apartheid Era - Konstantinos Margaritis (CES Working Papers, 2012)
South Africa was always a main interest region for European countries. The United Kingdom, the Netherlands, France and many others at lesser extent, tried to establish control over the country due to its special geographical position. On the other hand, since 1948, South Africa had been characterized by a tremendous regime, the so-called apartheid. The idea of this paper is to clarify the position of certain European countries towards South Africa during this severe period for the latest and to outline the major development agreements between the EC/EU and South Africa after the fall of apartheid, since South Africa is an important trade partner for the Union.
Keywords: F53; K33; Z18; F54; 330; Apartheid policy; European Union external relations; development policy; South Africa Romania